2009
DOI: 10.1074/jbc.m806137200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Dihydrouridine Synthase 2 from Yeast and the Importance of Modifications for Efficient tRNA Reduction

Abstract: Dihydrouridine synthases (DUSs) are flavin-dependent enzymes that catalyze site-specific reduction of uracils in tRNAs. The mechanism of DUS 2 from Saccharomyces cerevisiae was studied. Previously published turnover rates for this DUS were very low. Our studies show that the catalytic cycle consists of reductive and oxidative half-reactions. The enzyme is reduced by NADPH rapidly but has a very slow oxidative half-reaction using in vitro transcribed tRNA substrates. Using tRNA Leu purified from a DUS 2 knockou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
52
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 22 publications
(31 reference statements)
8
52
0
Order By: Relevance
“…We recently found that TthDus expressed in E. coli forms a stable complex with tRNA in cells that cannot be dissociated even on SDS-PAGE (12). Rider, et al also reported similar results (11). In the present study, TthDus and Tth-tRNA Phe were coexpressed in E. coli and their complex was purified for structure analysis.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…We recently found that TthDus expressed in E. coli forms a stable complex with tRNA in cells that cannot be dissociated even on SDS-PAGE (12). Rider, et al also reported similar results (11). In the present study, TthDus and Tth-tRNA Phe were coexpressed in E. coli and their complex was purified for structure analysis.…”
Section: Resultssupporting
confidence: 81%
“…Moreover, G19-C56 base pairing is prone to disruption in the transcripts as compared to modified tRNAs (18). Several previous studies indicated that Dus targets tRNA containing modifications (11,16). In this study, we showed that Dus can bind with tRNA that already has modifications other than D, but cannot recognize transcribed tRNA despite having the identical sequence (Fig.…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…S1A). The formation of dihydrouridine is catalyzed by dihydrouridine synthases (Dus) (10)(11)(12). Different Dus subfamilies display specificity toward distinct subsets of target uridines in tRNA.…”
mentioning
confidence: 99%
“…[4 S - 2 H]-NADPH was synthesized from [1- 2 H]glucose/hexokinase/glucose-6-phosphate dehydrogenase (13). …”
Section: Methodsmentioning
confidence: 99%